Inhomogeneous travelling-wave accelerating sections and WKB approach - Ayzatsky, M.I. (Вопросы атомной науки и техники, 2021)
The paper presents the results of a study of the possibility of using the WKB approach to describe Inhomogeneous Travelling-Wave Accelerating Sections. This possibility not only simplifies the calculation, but also allows the use of simpler physical models of transient processes. Using the traveling wave concept simplifies the understanding of pulsed-excited ITWAS transients and the development of methods to mitigate their effect on beam parameters. Представлено результати дослідження можливості використання ВКБ-підходу для опису неоднорідних прискорюючих секцій на хвилі, що біжить. Ця можливість не тільки спрощує розрахунок, а й дозволяє використовувати більш прості фізичні моделі перехідних процесів. Використання концепції біжної хвилі спрощує розуміння перехідних процесів у секціях з імпульсним збудженням і розробку методів зменшення їх впливу на параметри пучка. Представлены результаты исследования возможности использования ВКБ-подхода для описания неоднородных ускоряющих секций на бегущей волне. Эта возможность не только упрощает расчет, но и позволяет использовать более простые физические модели переходных процессов. Использование концепции бегущей волны упрощает понимание переходных процессов в секциях с импульсным возбуждением и разработку методов уменьшения их влияния на параметры пучка.